Lateral hypothalamus lesions influences water and salt intake, and sodium and urine excretion, and arterial blood pressure induced by L-NAME and FK 409 injections into median preoptic nucleus in conscious rats - Saad, W. A.; Guarda, IFMS; Camargo, LAD; Garcia, G.; Gutierrez, L. I.; Simoes, S.; Guarda, R. S. (Elsevier B.V., 2004)
Male Holtzman rats weighting 200-250 g were anesthetized with zoletil 50 mg/Kg (tiletamine chloridrate 125,0 mg and zolazepan chloridrate 125,0 mg) into quadriceps muscle and submitted an electrolytic lesion of the lateral hypothalamus (LH) and a stainless steel cannula was implanted into their median preoptic nucleus (MnPO). We investigated the effects of the injection into the (MnPO) of FK 409 (20 mug/0.5 mul), a nitric oxide (NO) donor, and N-W-nitro-L-arginine methyl ester (L-NAME) 40 mug/0.5 mul, a nitric oxide synthase inhibitor (NOSI), on the water and sodium appetite and the natriuretic, diuretic and cardiovascular effects induced by injection of L-NAME and FK 409 injected into MnPO in rats with LH lesions. Controls were injected with a similar volume of 0.15 M NaCl. L-NAME injected into MnPO produced an increase in water and sodium intake and in sodium and urine excretion and increase de mean arterial pressure (MAP). FK 409 injected into MnPO did not produce any change in the hydro electrolytic and cardiovascular parameters in LH-sham and lesioned rats. FK 409 injected before L-NAME attenuated its effects. These data show that electrolytic lesion of the LH reduces fluid and sodium intake as well as sodium and urine excretion, and the pressor effect induced by L-NAME. LH involvement with NO of the MnPO excitatory and inhibitory mechanisms related to water and sodium intake, sodium excretion and cardiovascular control is suggested. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: central nervous system; L-NAME; FK 409; water; sodium; blood pressure